2014
DOI: 10.1016/j.memsci.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Rejection and fate of trace organic compounds (TrOCs) during membrane distillation

Abstract: In this study, we examined the feasibility of membrane distillation (MD) for removing trace organic compounds (TrOCs) during water and wastewater treatment. A set of 29 compounds was selected to represent major TrOC groups, including pharmaceuticals, steroid hormones, phytoestrogens, UV-filters, industrial chemicals, and pesticides that occur ubiquitously in municipal wastewater. Results reported here suggest that rejection and fate and transport of TrOC during MD are governed by their volatility and, to a les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 43 publications
3
71
1
Order By: Relevance
“…In recent years, MD displays a very good application prospect in desalination [3][4][5]. Compared with conventional desalination processes such as nanofiltration (NF), reverse osmosis (RO) and thermal evaporation, MD can utilize waste heat of low quality, treat wastewater containing higher salt concentration [6][7][8], and even remove some organics that used to be difficult to remove [9][10][11]. According to the adopted condensation methods, the MD systems can be classified into four different categories: direct contact membrane distillation (DCMD), air gap membrane distillation (AGMD), sweeping gas membrane distillation (SGMD) and vacuum membrane distillation (VMD) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, MD displays a very good application prospect in desalination [3][4][5]. Compared with conventional desalination processes such as nanofiltration (NF), reverse osmosis (RO) and thermal evaporation, MD can utilize waste heat of low quality, treat wastewater containing higher salt concentration [6][7][8], and even remove some organics that used to be difficult to remove [9][10][11]. According to the adopted condensation methods, the MD systems can be classified into four different categories: direct contact membrane distillation (DCMD), air gap membrane distillation (AGMD), sweeping gas membrane distillation (SGMD) and vacuum membrane distillation (VMD) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of these are concerned with industrial chemicals such as benzene [60] and trichloroethylene [61] at an elevated feed concentration. Two recent studies by Wijekoon et al, [62,63] are the only exception.…”
Section: Membrane Distillationmentioning
confidence: 97%
“…Wijekoon et al, [62] = Vapour pressure×MW/water solubility. Wijekoon et al, [62] showed that all TrOCs with pK H > 9 (which can be classified as non-volatile) were well removed by MD.…”
Section: Membrane Distillationmentioning
confidence: 99%
See 2 more Smart Citations